TANTANGAN TRADISI VS. MODERNITAS DALAM NOVEL KENANGA KARYA OKA RUSMINI: TINJAUAN ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH - Anggraini, Lisa; Rosa, Rosa Putri Theresia Sinaga; Nurul , Nurul Atikah; Chairunisa, Hera (Asosiasi dosen IDEBAHASA KEPRI, 2024)
This research aims to resolve the conflict between tradition and modernity as well as gender injustice expressed in the novel Kenanga by Oka Rusmini. Using a discourse approach, this research describes how the characters struggle to maintain their identity and cultural values ​​in the midst of modernization, as well as resistance to traditional norms that limit women's freedom in Balinese society. In the context of this novel, the conflict between tradition and modernity is reflected through character characterization, plot development, and use of language. This research also detects resistance and gender emancipation efforts made by the characters in the novel. It is hoped that the research results can provide a theoretical contribution in expanding understanding of the dynamics between the conflict between tradition and modernity in Bali as well as contribute to the study of Indonesian literature by providing an in-depth analysis of a contemporary literary work.